2023
DOI: 10.21037/jtd-22-1283
|View full text |Cite
|
Sign up to set email alerts
|

Simplified total arch reconstruction with a stented graft for extended aortic arch dilation

Abstract: Background: Reconstruction of the aortic arch and its three supra-aortic vessels remains a great surgical challenge with postoperative complications. We present a simplified total arch reconstruction with a modified stent graft (s-TAR) and compared its operative outcomes with conventional total arch replacement (c-TAR).Methods: This retrospective analysis of prospectively collected data from all consecutive patients who had ascending aortic aneurysm with extended aortic arch dilation and underwent simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the mainstream surgical approach for the three supra-aortic branches is hindered by complicated procedures, high time consumption, and significant surgical trauma [ 13 ]. Previously, our team introduced a simplified total arch reconstruction method for extended aortic arch dilation, which yielded satisfactory operative results [ 14 ]. To simplify the procedure and reduce the risk of serious complications associated with TAAD, we designed an innovative in-situ stent-graft fenestration (ISSF) technique for minimally invasive aortic arch reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mainstream surgical approach for the three supra-aortic branches is hindered by complicated procedures, high time consumption, and significant surgical trauma [ 13 ]. Previously, our team introduced a simplified total arch reconstruction method for extended aortic arch dilation, which yielded satisfactory operative results [ 14 ]. To simplify the procedure and reduce the risk of serious complications associated with TAAD, we designed an innovative in-situ stent-graft fenestration (ISSF) technique for minimally invasive aortic arch reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al recently reported on a simplified approach to open total arch replacement (s-TAR) using a physician-modified stent graft ( 1 ). In the s-TAR procedure, the authors replace the ascending aorta with a Dacron graft, and then perform antegrade deployment of a stent graft under circulatory arrest with antegrade selective cerebral protection.…”
mentioning
confidence: 99%